Project for Strengthening the Profile of Pancasila Students (P5) Eco Print Creation: The Role of Students of Kampus Mengajar Program Batch 6 - Widiansyah, Apriyanti; Fitriansyah, Fifit; Gildore, Phyll Jhann E (IJIS Edu : Indonesian Journal of Integrated Science Education, 2024)
The Program Kampus Mengajar not only carries out the mission of numeracy literacy, but also contributes to every activity in implementing the independent curriculum, one of which is the the Projek Penguatan Profil Pelajar Pancasila (P5). Through the development of the Pancasila Student Profile which contains the characters and competencies needed to become good world citizens, it needs to be introduced from an early age, at all levels of education. The aim of this research is to see the role of teaching campus students in carrying out P5 activities at SDN Petukangan Selatan 05 in making eco prints using the pounding technique. The research method used is a qualitative approach, namely by describing the conditions of P5 activities descriptively. The results of this research are that P5 activities by making eco prints make students more active, creative and create space for imagination by utilizing the environment around the school. The novelty of this research is that the P5 program is currently happening in the independent curriculum so that the research follows current trends.